Soluble Urokinase Plasminogen Activator Receptor is Associated with Coronary Artery Calcification and Cardiovascular Disease in Patients Undergoing Hemodialysis - Wenjuan Wu; Yanhai Cui; Juan Hu; Ruyi Liao; Sijia Li; Liyi Mo; Lixia Xu; Yuanhan Chen; Zhiwen Lian; Xiulan Tian; Zhuo Li; Ruizhao Li; et al. (Karger Publishers, 2018)
Background/Aims: Cardiovascular disease (CVD) is an important cause of morbidity and mortality in hemodialysis patients. Vascular calcification is thought to play an important role in causing CVD. Soluble urokinase plasminogen activator receptor (suPAR) is a biomarker strongly predictive of cardiovascular outcomes in the pathogenesis of diabetic patients with renal disease treated with hemodialysis. We investigated the relationship between suPAR and coronary artery calcification (CAC) in patients undergoing maintenance hemodialysis. Methods: A total of 99 adult hemodialysis patients were enrolled in this study. Plasma samples were analyzed for suPAR with an enzyme-linked immunosorbent assay and the CAC score was determined with multidetector computed tomography. The occurrence of cardiovascular events and all-cause mortality during follow-up were recorded from January 1, 2010 to June 1, 2016. Results: In 99 patients treated with maintenance hemodialysis, 91 (91.9%) had varying degrees of CAC, and suPAR correlated positively with the CAC score in a Spearman analysis. In a mean follow-up period of 33 months, 36 patients (36.4%) experienced at least one cardiovascular event. When the quartiles of suPAR concentrations were used as the cutoff points for a subgroup analysis, the incidence of CVD and all-cause mortality was much higher in the higher quartiles of suPAR. In a univariate Cox regression analysis, high suPAR was a risk factor for CVD and all-cause mortality. Conclusion: suPAR is associated with the CAC score and is a risk factor for new-onset CVD in patients undergoing hemodialysis.